Lifting the iron curtain of vision - Boris Rosin; Jose‐Alain Sahel (EMBO Molecular Medicine)
Abstract Ocular and specifically retinal toxicities of systemic medications are prevalent and encompass many disease modalities. For many of these pharmaceuticals, established follow‐up protocols are in place to ensure timely detection and cessation of therapy. However, while for some disorders, cessation of therapy is a viable option due to existing treatment alternatives, for some others cessation of treatment can be life threatening and/or shorten the patient's life expectancy. Such is the case for iron chelating agents used in transfusion‐dependent patients of Thalassemia, of which deferoxamine (DFO) is the most widely used. In their recent article in EMBO Molecular Medicine, Kong et al (2023) addressed the issue of DFO‐induced retinal toxicity used both in vivo and in vitro techniques. Their study suggests a potentially protective role for α‐ketoglutarate (AKG) supplementation against DFO toxicity.